2020
DOI: 10.1074/jbc.ra119.011658
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol kinase stimulates uncoupling protein 1 expression by regulating fatty acid metabolism in beige adipocytes

Abstract: Browning of adipose tissue is induced by specific stimuli such as cold exposure and consists of up-regulation of thermogenesis in white adipose tissue. Recently, it has emerged as an attractive target for managing obesity in humans. Here, we performed a comprehensive analysis to identify genes associated with browning in murine adipose tissue. We focused on glycerol kinase (GYK) because its mRNA expression pattern is highly correlated with that of uncoupling protein 1 (UCP1), which regulates the thermogenic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 49 publications
(3 reference statements)
0
11
0
Order By: Relevance
“…Kyoto Encyclopedia of Genes and Genomes analysis revealed a significant enrichment of glycerolipid metabolism, as well as glycine, serine, and threonine metabolism as a feature of cold-induced gene patterns ( Figure 7A ). qPCR analysis confirmed the increase in mRNA levels of aminolaevulinic acid synthase 2 (ALAS2), the rating-limiting enzyme in heme synthesis which can maintain the mitochondrial function in brown adipocytes ( Galmozzi et al, 2019 ), as well as glycerol kinase (Gyk), which catalyzes the phosphorylation of glycerol to glycerol 3-phosphate and is reported to be involved in UCP1 level induction ( Iwase et al, 2020 ), in cold-treated iWAT versus CL treatment ( Figure 7C ). Meanwhile, we noted that pyruvate metabolism, carbon metabolism, and glycolysis were uniquely enriched in CL treatment, suggesting that in addition to oxidative phosphorylation, fatty acid metabolism, and TCA cycle that were commonly regulated by cold and CL, CL treatment features active glucose mobilization for energy demands ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Kyoto Encyclopedia of Genes and Genomes analysis revealed a significant enrichment of glycerolipid metabolism, as well as glycine, serine, and threonine metabolism as a feature of cold-induced gene patterns ( Figure 7A ). qPCR analysis confirmed the increase in mRNA levels of aminolaevulinic acid synthase 2 (ALAS2), the rating-limiting enzyme in heme synthesis which can maintain the mitochondrial function in brown adipocytes ( Galmozzi et al, 2019 ), as well as glycerol kinase (Gyk), which catalyzes the phosphorylation of glycerol to glycerol 3-phosphate and is reported to be involved in UCP1 level induction ( Iwase et al, 2020 ), in cold-treated iWAT versus CL treatment ( Figure 7C ). Meanwhile, we noted that pyruvate metabolism, carbon metabolism, and glycolysis were uniquely enriched in CL treatment, suggesting that in addition to oxidative phosphorylation, fatty acid metabolism, and TCA cycle that were commonly regulated by cold and CL, CL treatment features active glucose mobilization for energy demands ( Figure 7B ).…”
Section: Resultsmentioning
confidence: 72%
“…In the face of energy demand, for example, during cold or CL stimulation, TG breaks into glycerol and fatty acid ( Beale et al, 2002 ) to provide energy substrates. Via transcriptome data and qPCR confirmation, we confirmed that Gyk, an enzyme critical for glycerol/fatty acid metabolism and UCP1 induction partially through the β3AR-cAMP-CREB pathway ( Iwase et al, 2020 ), was upregulated upon cold exposure, indicating a critical role of lipid metabolism in cold-stimulated browning. Besides, we found that compared to CL treatment, cold exposure specifically promoted glycerolipid metabolism that is an integral part of the glycerolipid/FFA cycle essential for maintaining body temperature by releasing heat at the expense of ATP ( Prentki and Madiraju, 2008 ).…”
Section: Discussionmentioning
confidence: 68%
“…Isoproterenol stimulation not only increases the expression of Ucp1 , but also genes related to beige adipocyte function ( Fgf21 , Pgc1α , Cidea , and Dio2 ) by activating PKA signaling [ [28] , [29] , [30] , [31] ]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ECL immunoblotting clarity system (Bio-Rad) was used to visualize the bands, detected under ChemiDoc TM Touch imaging system (Bio-Rad, California, United States). Band density was analyzed using Image Lab software (Bio-Rad, California, United States) and normalized according to the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) content ( Iwase et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%